Museum Angkut Virtual Tour Dengan Optimasi Penelusuran Menggunakan Algoritma A-Star - Muhammad Januar Wicaksono; Istiadi Istiadi; Indra Dharma Wijaya; Fitri Marisa; Syahroni Wahyu Iriananda (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2021)
In the midst of competition for tourist rides nowadays, the developers are required to be creative and innovative in order to attract potential tourist. The most common way is promotion through mainstream media by sharing photo galleries from several points of view in those tourist rides that is considered the most interesting. From the photo galleries, the potential tourist can decide to travel or cancel their plans. Unfortunately, sometimes tourists feel that the actual location is not as expected as shown in photos gallery promotions before. To avoid this incident in Museum Angkut, it needs to build a virtual tour applications as a form of promotion that can describe real sightings are more alive than just photos. Meanwhile for in-app directions, then added the A-Star algorithm with a Manhattan count that can help users to find objects in the virtual tour. The result of this research is the presence of the Museum Angkut Virtual Tour application that has been tested in the field and obtained quantitative data with a score of 82% of prospective tourist respondents are agree with the making of this application.Kata kunci— Virtual Tour, Unity, A-Star, Promotion Media, Optimal Device Specs.